Plant Growth Stage Drives the Temporal and Spatial Dynamics of the Bacterial Microbiome in the Rhizosphere of Vigna subterranea - Ajilogba, Caroline Fadeke; Olanrewaju, Oluwaseyi Samuel; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2022)
Bambara groundnut (BGN) is an underutilized legume commonly found in sub-Saharan Africa. It thrives in marginal soils and is resistant to drought stress. Several studies have been carried out on the nutritional properties of BGN, but very little is known about the effects of plant growth changes and development on rhizosphere bacterial dynamics and function. This study reports on the bacterial dynamics and function in the bulk and rhizosphere soils of BGN at different growth stages (vegetative, flowering, pod-filling, and maturation stages). Aside from the maturation stage that shows distinct community structure from the other growth stages, results obtained showed no significant differences in bacterial community structure among the other growth stages. At a closer level, Actinobacteria, Proteobacteria, and Acidobacteria were dominant in rhizosphere soils at all growth stages. The bulk soil had the least average phyla abundance, while the maturity stage was characterized by the highest average phyla abundance. Rubrobacter, Acidobacterium, and Skermanella were the most predominant genus. It was observed from the analysis of operational taxonomic units that there was significant change in the bacterial structure of the rhizosphere with a higher abundance of potential plant growth-promoting rhizobacteria, at the different growth stages, which include the genera Bacillus and Acidobacterium. Biomarker analysis revealed 7 and 4 highly significant bacterial biomarkers by linear discriminant analysis effect size and random forest analysis at the maturation stage, respectively. The results obtained in this study demonstrated that the bacterial communities of BGN rhizosphere microbiome dynamics and function are influenced by the plant’s growth stages.